The Collapse of Syria: A Case of the failure of Counter-Insurgency (COIN) from Clausewitz Trinity Perspective - Sitompul, Martua; Hendra, Afrizal (The Eastasouth Journal of Social Science and Humanities, 2025)
The Syrian conflict, beginning in 2011, escalated into a complex civil war, challenging the government's counterinsurgency (COIN) efforts. This study analyzes Syria's COIN failure through Clausewitz's Trinity, focusing on the interplay between government, military, and people. Using qualitative document analysis, data from government reports, academic articles, and expert analyses are examined. The research highlights an imbalance in Clausewitz's Trinity: the Assad regime lost legitimacy, the military fragmented, and excessive reliance on force alienated civilians. External support for rebels further hindered COIN efforts. The study underscores the need for balanced COIN strategies, integrating military action, government legitimacy, and popular support. These insights offer valuable lessons for addressing future insurgencies with a holistic approach.